(untitled) (Anclajes, 2020)
This article focuses on two novels by the French author Georges Perec (1936-1982) where the main characters are art forgers. In Portrait of a Man Known as Il Condottiere (1957-1960) a non-achieved story of counterfeiting is developed, while in A Gallery Portrait (1979) a family makes gallery owners, collectors and museums acquire fake works. The passage from one text to another represents a conceptual development in the author’s literature where, besides questioning the myths of originality and uniqueness, Georges Perec proposes to establish a relationship with the works of art that goes from history to memory.